PERFORMAN “ITIK CILI” (PERSILANGAN ITIK PEKING X ITIK BALI) UMUR 1-9 MINGGU YANG DIBERI RANSUM KOMERSIAL DAN RANSUM BUATAN DIBANDINGKAN ITIK BALI - Ambara, Agus Arik; Suparta, I N.; Suasta, I M. (Jurnal Peternakan Tropika, 2014)
This study aims to determine the level of growth, carcass production and conversion ransum "cili duck" than bali duck, and to know the effect of commercial ransum and artificial ransum ??with the same nutrient composition of the growth rate, carcass production and conversion ratio "cili duck" age of 1 -9 weeks. The experiment was conducted in the village of Perean Tengah, Tabanan which lasted for 8 weeks. Research using completely randomized design (CRD) with three treatments and six replications. The three treatments were: "cili duck" with a commercial ransum CP 511 (A), "cili duck" with artificial ransum (B), and (control) bali duck with commercial ransum CP 511 (C). The results showed that the average final weight, weight gain, and carcass weights at treatment C significantly more lower (P <0,05) of treatment A and B. Mean final weight, weight gain, and carcass weights in treatment A was significantly higher (P <0,05) than treatment B. Average consumption ransum treatment C was not significantly different (P> 0,05) lower than treatment B but significantly different (P <0,05) lower than treatment A. The average consumption ransum treatments were not significantly different (P> 0,05) higher than treatment B. Average conversion ratio C treatment were significantly different (P <0,05) higher than that of treatment A and B. Mean treatment A conversion ratio was not significantly different (P> 0,05) lower than treatment B. Based on the research it can be concluded (1). "cili duck" (a hybrid of peking duck x bali duck ) has a level of growth and carcass production better than the bali duck, (2). Maintenance "cili duck" aged 1-9 weeks, rationing commercial CP 511 can generate the growth rate, higher carcass production and efficient use of ransum better than artificial rationing, (3). "cili duck" has a ransum efficiency better than the bali duck.
Keywords: Growth level, carcass production, feed efficiency, bali duck, “cili duck”